Impresi Reformasi Kurikulum Merdeka pada Kualitas Pembelajaran - Muhammad Safii Siregar; Moch. Iqbal (Simpati, 2024)
The Independent Curriculum reform in Indonesia was implemented as a response to the need for more relevant and adaptive education. This research aims to analyze the influence of curriculum reform on the quality of learning in schools in Indonesia. The method used is literature study by taking data from journals. The research results show that the implementation of the Merdeka Curriculum increases student engagement, creativity and better learning outcomes. Apart from that, teachers also experience improvements in teaching methodology and classroom management. This research provides important insights for future education policy development, by emphasizing the importance of teacher training and systemic support in curriculum implementation.